Hospital Staff Well-Being: Examining Workload, Distributive Justice, and the Moderating Role of Social Support - Rizfiyah Desita Indriyani; Fuji Adiningsih; Dedi Muhammad Siddiq; James Tembo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the influence of workload and distributive justice on employee well-being, with social support examined as a moderating variable. Grounded in the Job Demands–Resources (JD-R) Model and Equity Theory, the research focuses on private hospital staff in Indramayu, Indonesia a high-pressure healthcare setting. A quantitative explanatory design was employed, using web-based self-report questionnaires completed by 178 respondents. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) version 4.0. The findings reveal that workload negatively and significantly affects employee well-being, while perceptions of distributive justice positively influence it. Furthermore, social support moderates both relationships by buffering the adverse effects of workload and amplifying the benefits of distributive justice. Employees who experience both fairness and strong social support tend to report higher psychological resilience and job satisfaction.